A Comprehensive Systematic Review of the Role of Semaglutide Anti-Obesity Therapy in Multiple Metabolic Diseases: A Systematic Review of Randomized Controlled Trials and Primary Studies - Jeffy Marta (The International Journal of Medical Science and Health Research, 2026)
Introduction: Obesity constitutes the pathophysiological hub of interconnected metabolic diseases including type 2 diabetes mellitus (T2DM), atherosclerotic cardiovascular disease (ASCVD), heart failure with preserved ejection fraction (HFpEF), chronic kidney disease (CKD), metabolic dysfunction-associated steatohepatitis (MASH) and peripheral artery disease (PAD). Semaglutide, a long-acting glucagon-like peptide-1 receptor agonist (GLP-1 RA), has been evaluated across all these domains. This systematic review synthesised primary evidence on semaglutide across multiple metabolic diseases to determine consistency of benefit across organ systems. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible designs comprised randomized controlled trials and observational studies evaluating semaglutide in obesity or obesity-related metabolic disease. Systematic reviews were excluded from primary tabulation but retained as contextual comparators. Two reviewers independently screened, extracted data and appraised risk of bias using Cochrane RoB 2 and ROBINS-I; certainty was graded with GRADE. Synthesis was narrative and semi-quantitative by outcome domain. Results: Twenty-seven primary studies (24 RCTs, 3 observational cohorts) encompassing >180,000 participants across 15 outcome domains were included. Semaglutide 2.4 mg weekly produced mean weight reductions of -14.9% to -16.0% versus -2.4% to -5.7% with placebo (all P<0.001). In prediabetes, 84.1-89.8% reverted to normoglycaemia versus 47.8-70.4% (P<0.0001). SELECT demonstrated 20% MACE reduction (HR 0.80; P<0.001) in obesity without diabetes; SOUL demonstrated 14% MACE reduction with oral semaglutide (HR 0.86; P=0.006). FLOW demonstrated 24% reduction in major kidney disease events (HR 0.76; P=0.0003) and 20% all-cause mortality reduction (HR 0.80; P=0.01). STEP-HFpEF demonstrated 7.5-point KCCQ-CSS improvement (P<0.0001). ESSENCE demonstrated steatohepatitis resolution in 62.9% versus 34.3% (P<0.001). STRIDE demonstrated walking distance improvement (ETR 1.13; P=0.0004). C-reactive protein fell 39-48%. Gastrointestinal adverse events occurred in 63.5-84.1% but were predominantly mild-to-moderate and transient, with permanent discontinuation in ~4-5%. Risk of bias was low for 20/24 RCTs; GRADE certainty was high for 11 domains. Discussion: Semaglutide demonstrates reproducible benefit extending beyond weight reduction into hard cardiovascular, renal, hepatic and functional outcomes. Mediation analyses attributed little treatment effect to weight change, implying direct vascular, anti-inflammatory and haemodynamic mechanisms. Benefit was largely independent of baseline BMI, HbA1c and comorbidity severity. Principal limitations include industry sponsorship, under-representation of non-White populations, and reversibility of benefit upon discontinuation. Conclusion: Semaglutide is a disease-modifying agent for the cardiovascular-kidney-metabolic syndrome. Treatment produced significant improvements in body weight, glycaemia, lipids, inflammation, MACE, heart failure, kidney disease, hepatic histology, functional capacity and all-cause mortality, with acceptable safety profile. It is recommended that semaglutide be positioned as first-line therapy in obesity with cardiovascular, renal or hepatic disease; that treatment be regarded as chronic; and that future research prioritise head-to-head incretin comparisons, non-industry-funded trials, and under-represented populations.